2012
DOI: 10.1364/oe.20.018646
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of effective refractive-index differences in a few-mode fiber by axial fiber stretching

Abstract: A method for measuring the effective refractive-index differences in a few-mode fiber by applying axial fiber stretching is described. This method represents a straightforward technique for characterization of few-mode fibers. Interference between LP01 and LP11 and in some cases also between LP11 and LP21 are observed in a fiber designed for support of LP01 and LP11. The relative strength of the coupled modes depends on specific splicing characteristics, and in some cases only two modes are seen. The results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The values of core radius (a) and the refractive Brought to you by | Purdue University Libraries Authenticated Download Date | 6/8/15 7:40 PM index of core (n 1 ) used in this context are 3.65 μm and 1.46 respectively. It is found that with increase of V number in both types of fiber, the effective index of refraction decreases indicating less delay for the fundamental mode for higher V. This is consistent with the results available in literature [19]. In Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The values of core radius (a) and the refractive Brought to you by | Purdue University Libraries Authenticated Download Date | 6/8/15 7:40 PM index of core (n 1 ) used in this context are 3.65 μm and 1.46 respectively. It is found that with increase of V number in both types of fiber, the effective index of refraction decreases indicating less delay for the fundamental mode for higher V. This is consistent with the results available in literature [19]. In Fig.…”
Section: Resultssupporting
confidence: 92%
“…The knowledge of effective index of refraction is required for system modeling, assembly of optical devices, selection of index matching gel so as to minimize joint losses and back reflection. Furthermore, as regards estimation of the interference between fundamental mode (LP 01 ) and first higher order mode (LP 11 ) in dual mode fiber, the corresponding effective indices of refraction need to be taken care of [19]. In case of Fiber Bragg grating Sensors, the importance of effective index of refraction is well established [20].…”
Section: Introductionmentioning
confidence: 99%
“…When an FMF supports propagating N modes, without considering mode-degeneracy, the FMF can sense in principle N different parameters. The operation principle of FMF-based multi-parameter sensors is mainly attributed to the different effective refractive index (n eff ) values of the non-degenerate spatial modes [31]. Consequently, for instance, the Bragg wavelength of a fiber Bragg grating (FBG) or Brillouin frequency shift (BFS) becomes highly mode-dependent in an FMF.…”
Section: Various Reactions Of Spatial Modes To External Parametementioning
confidence: 99%
“…Although physical lengths can be measured with extremely high precision in air [11], only the optical path length can be measured with extreme precision in optical fibers [12], and the measurement of an absolute fiber length with a relative accuracy better than 10 -4 at a controlled temperature and strain is not an attainable task in many cases. The measurement of modal phase indices in few modes or multimode fibers relies on the previous knowledge of the fundamental mode [13,14,15] since the measurement techniques only provide information on the index difference between modes. Fiber birefringence depends on the difference of two orthogonal refraction indices and can be measured with very high precision by interferometric or by OTDR techniques [16,17].…”
Section: Introductionmentioning
confidence: 99%